Síntese e caracterização do compósito SnFe2O4/polipirrol para utilização na degradação do corante tartrazina via processo foto-fenton - Leichtweis, Jandira (2019)
One of the major concerns with the environment and aquatic life is related to the discharge of effluents containing synthetic dyes. Among the most used synthetic dyes is tartrazine, a lemon yellow azo dye, used in the food coloring, cosmetics and textile industries. These wastewater can contain high coloration, moderate organic content, large amounts of toxic, not biodegradable and highly resistant in the environment, being difficult to degrade by conventional methods, making it impossible to reach the standards of release in river systems. As an alternative to the treatment of these liquid wastes, the advanced oxidative processes, notably the photo-Fenton process, which is the combination of a powerful oxidizing agent (such as H2O2), an iron-based photocatalyst (example ferrite) and UV-Vis radiation. However, studies report that a problem presented by semiconductor oxides, when employed pure as photocatalysts, is related to the high recombination rates that occur between the electron/hole pairs formed after activation. Thus, the use of supported photocatalysts is a technique applied to improve the photocatalytic performance of a semiconductor and to overcome this problem. In the present study, SnFe2O4 was synthesized and then an unprecedented composite was formed, supporting different masses of SnFe2O4 in polypyrrole (conductive polymer). Preliminary tests indicated a greater color reduction of tartrazine dye solution using the composite containing 10% of SnFe2O4 when compared to pure SnFe2O4 and in percentages of 5 and 15%. The characterization of the samples demonstrated that the SnFe2O4 can be inside the pores of the polypyrrole, suggesting the formation of the composite. The main operational parameters of the reaction such as pH and H2O2 concentration were evaluated using a laboratory-scale photoreactor exposed in artificial UV-Vis irradiation. Color reduction was chosen as the response variable. pH 3 and 34 μL H2O2 concentration demonstrated higher efficiency, removing 98% of the color in 60 minutes. This may be linked to the formation of Fenton reagents under acid conditions (generation of •OH radicals) and to the fact that very high or very low concentrations of H2O2 do not favor the process. The recycle of the material showed that it is stable, presenting high efficiencies after eight reuses. The photo-Fenton process with artificial light was compared with the solar, demonstrating color removal efficiency in both processes. A capture of the main radicals was performed, evidencing that the radicals • O2 - and •OH act in the photo-Fenton process. After the chromatography analysis it was possible to verify the degradation of the molecule in fragments of lower mass. Finally, a mechanism was suggested based on the results obtained. Based on all characterizations and tests of catalytic activity, this composite has promising activity against the degradation of aqueous pollutants.